Pengaruh Kompetensi, Motivasi Kerja dan Kepuasan Kerja terhadap Kinerja Dosen - Hari Wahyuni (University of Merdeka Malang, 2019)
The purposes of this study are to determine and analyze the influence of competence, work motivation and job satisfaction on the performance of lecturer at Merdeka University Pasuruan. Data analysis uses a quantitative analysis. Population in this research are all permanent lecturers at Universitas Merdeka Pasuruan as 43 lecturers. Sample taken by census method. The results of research show that: 1) competence has a significant influence on the performance of lecturer, 2) work motivation has a significant influence on the performance of lecturer, 3) job staisfaction has a significant influence on the performance of lecturer, 4) job satisfaction has a dominant effect on lecturer performance. https://doi.org/10.26905/jmdk.v7i2.3245